2x-5(x-3)=-8+4x+9

Simple and best practice solution for 2x-5(x-3)=-8+4x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-5(x-3)=-8+4x+9 equation:


Simplifying
2x + -5(x + -3) = -8 + 4x + 9

Reorder the terms:
2x + -5(-3 + x) = -8 + 4x + 9
2x + (-3 * -5 + x * -5) = -8 + 4x + 9
2x + (15 + -5x) = -8 + 4x + 9

Reorder the terms:
15 + 2x + -5x = -8 + 4x + 9

Combine like terms: 2x + -5x = -3x
15 + -3x = -8 + 4x + 9

Reorder the terms:
15 + -3x = -8 + 9 + 4x

Combine like terms: -8 + 9 = 1
15 + -3x = 1 + 4x

Solving
15 + -3x = 1 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
15 + -3x + -4x = 1 + 4x + -4x

Combine like terms: -3x + -4x = -7x
15 + -7x = 1 + 4x + -4x

Combine like terms: 4x + -4x = 0
15 + -7x = 1 + 0
15 + -7x = 1

Add '-15' to each side of the equation.
15 + -15 + -7x = 1 + -15

Combine like terms: 15 + -15 = 0
0 + -7x = 1 + -15
-7x = 1 + -15

Combine like terms: 1 + -15 = -14
-7x = -14

Divide each side by '-7'.
x = 2

Simplifying
x = 2

See similar equations:

| 3d-8=-6+6 | | 7a+a=24 | | 8x-40+2x=180 | | 6(3x-9)-7=6(x-3)+41 | | A+10=98 | | 0=16t^2-10t+50 | | 28000+3000x=4250x+18000 | | (2y+9)(2y+9)=225 | | 49x-27=2-1.5x | | cosh(iaz)=1 | | 9.95m+.05=12 | | 6t(-8)=48 | | -5p+3+6p=9 | | 28000+3000x=-1750x+18000 | | 2+2x+2x=-34 | | -(-2-r)+2(-4r-3)=3 | | 28000+3000x=1750x+18000 | | 18+4n=20 | | 6-3(x-5)=4 | | .50d-5=2 | | 28000+3000x=1250x+18000 | | 3(x-4)+20=38 | | 9x^2-27x+8=0 | | -3y-12=-6 | | 12X-4y=9 | | 24y+60=-5-6 | | 6-6b+b+5=1-3b | | 28000+3000x=7000x+18000 | | 49x-27=2-1.5 | | -(4m-3)=-3(m-2) | | 28000+3000x=6000x+18000 | | 28000+3000x=8000x+18000 |

Equations solver categories